2006
DOI: 10.1186/1746-6148-2-2
|View full text |Cite
|
Sign up to set email alerts
|

A molecular epidemiological study of rabies epizootics in kudu (Tragelaphus strepsiceros) in Namibia

Abstract: BackgroundA panel of 37 rabies virus isolates were collected and studied, originating mainly from the northern and central regions of Namibia, between 1980 and 2003.ResultsThese virus isolates demonstrated a high degree of genetic similarity with respect to a 400 bp region of the nucleoprotein gene, with the virus isolates originating from kudu antelope (n = 10) sharing 97.2–100% similarity with jackal isolates, and 97–100% similarity with those isolated from domestic dogs. Phylogenetic analysis suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…We note that there are no domestic dogs in ENP and that there are no towns within 100km of Okaukuejo. The phylogenetic results indicated that the recent virus isolates are part of the same dog-jackal cycles as previously described (Mansfield et al, 2006). …”
Section: Discussionsupporting
confidence: 73%
“…We note that there are no domestic dogs in ENP and that there are no towns within 100km of Okaukuejo. The phylogenetic results indicated that the recent virus isolates are part of the same dog-jackal cycles as previously described (Mansfield et al, 2006). …”
Section: Discussionsupporting
confidence: 73%
“…Transmission from animals to humans is primarily through bites and contact with secretions–although bats have been implicated in relatively few cases (23, 24). Vampire bats are the reservoir hosts of rabies in the West Indies and some South American countries, but these have not been reported in Namibia.…”
Section: Viral Diseasesmentioning
confidence: 99%
“…A few previous studies have included partial nucleoprotein gene sequencing of Namibian and other southern African RABV isolates and a sizeable collection of sequences can be found in Genbank [12], [16], [17]. We therefore chose to continue with this sequence region in our analyses of the 49 new isolates from kudu and jackal (35 kudu and 14 jackal) (Table 1) from regions throughout Namibia (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Experimental observations of RABV in kudu have suggested that transmission could occur via non-bite means and that the mucosal surfaces of kudu are particularly susceptible to infection [11]. An earlier epidemiological study did consider molecular phylogeny, but included limited sample numbers that did not allow for definitive conclusions about the independence of the kudu rabies cycle [12]. Thus, although the maintenance of an independent RABV cycle in Namibian kudu has been speculated, we intended to provide additional evidence - based on genome sequence properties - that horizontal transmission of rabies among Namibian kudu is indeed a common occurrence.…”
Section: Introductionmentioning
confidence: 99%